PENGARUH KOMPENSASI, DISIPLIN KERJA DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. ERA PERMATA SEJAHTERA BANDA ACEH - Masyithah, Syarifah Mauli; muhammad, Muhammad; Yunidar, Syafira; Sabiran, Sabiran (SI-MEN, 2024)
This study is aimed to analyze the influence of compensation, work discipline and motivation toward the employee work productivity at PT. Era Permata Sejahtera Banda Aceh. The sample of this study was 20 employees. The result of the partial test on compensation influenced the employee work productivity at PT. Era Permata Sejahtera Banda Aceh. Work discipline influenced employee work productivity at PT. Era Permata Sejahtera Banda Aceh. However, motivation did not influence the employee work productivity at PT. Era Permata Sejahtera Banda Aceh. Furthermore, the Simultaneous Test among compensation, work discipline and motivation significantly affected the employee work productivity at PT. Era Permata Sejahtera Banda Aceh. As the result, compensation partially has an effect on the employee work productivity at PT. Era Permata Sejahtera Banda Aceh with a value of tcount (3,989) which is greater than ttable (1,662). Work discipline partially influenced the employee work productivity at PT. Era Permata Sejahtera Banda Aceh with a value of tcount (4,364) more than the value of ttable (1,662). Motivation partially did not affect the employee work productivity at PT. Era Permata Sejahtera Banda Aceh with a value of tcount (1,989) more than the value of ttable (1,662). Moreover, competency, work discipline and motivation have simultaneously affected the employee work productivity at PT. Era Permata Sejahtera Banda Aceh with a value of Fcount (43,486) greater than Ftable (2,709).